Impact of leadership styles on employee motivation as mediated by organizational culture: A case of healthcare NGO in Zambia - Lameck Chirwa (International Journal of Academe and Industry Research)
This study aimed to determine the impact of leadership styles on staff motivation in Zambian healthcare non-governmental organizations (NGOs) using organizational culture as a mediator. A quantitative survey with a sample size of 286 employees was undertaken, and multiple regression analysis was utilized to examine the impact of transformational, transactional, democratic, and autocratic leadership styles on employee motivation. Transformational leadership had the strongest positive influence on motivation (β = 1.275, p < 0.001), while transactional leadership negatively affected motivation (β = -0.403, p = 0.015). Organizational culture had an important role in mediating these interactions (β = 0.721, p = 0.002). The study emphasizes the importance of transformational leadership in non-governmental organizations (NGOs) and shows that cultivating a strong organizational culture increases employee engagement. This study makes both theoretical and empirical contributions to the literature on leadership styles and employee motivation, as it is among the few to incorporate organizational culture as a mediating variable in the context of health NGOs in low and middle-income countries. The study's limitation is its inability to be generalized to different populations due to the use of a convenience sample strategy for data collection. For future research, we recommend mixed-method techniques, greater sample sizes, and stratified random sampling to ensure diverse representation and deeper contextual insights.